Crescimento econômico e restrição externa: evidências empíricas na economia brasileira (1991-2010) - Silva, Andrei de Lima e (2013)
This study aims to investigate the influence of the balance of payments constrained on economic growth in Brazil from 1991 to 2010. With this order, are shown some of the Keynesian balance of payments constrained growth models, inspired by Thirlwall (1979) and Kaldor (1970), which are supported by important points in common, such as adherence to the principle of effective demand. Given that within this theoretical perspective, there is no consensus about the best model to explain the growth rate allowed by the balance of payments constraint, the results are presented by the representative of the empirical literature that addresses the topic, which are necessary for understand the Brazilian case. From the estimation of the income elasticity of imports (0.85) via autoregressive vectors with error correction (VEC), it was calculated five growth rates of income, as predicted by the models of Thirlwall (1979), Thirlwall and Hussain (1982), Moreno-Brid (1998, 2003) and Lourenço et al. (2011) and compared with the actual growth rate. The empirical analysis has shown that: it can not reject the presence of external constraint in the Brazilian economy, there is a strong similarity in growth rates provided by different modeling suggest that growth with external constraint. In addition, when using data in quarterly for the period after 1990 there are no factors that could cause instability in the parameters of the import function (income elasticity and price elasticity of imports) within the period, which indicates that the structural break widely associated with the year 1994 was not confirmed by this study